2008
DOI: 10.1364/josab.25.000651
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon spectra of nanospheres under a tightly focused beam

Abstract: We study the modification of the far-field cross sections and the near-field enhancement for gold and silver nanospheres illuminated by a tightly focused beam. Using a multipole-expansion approach we obtain an analytical solution to the scattering problem and provide insight on the effects of focusing on the optical response. Large differences with respect to Mie theory are found especially when the nanoparticle supports quadrupole or higher-order resonances. * Electronic address: mario.agio@phys.chem.ethz.ch … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 46 publications
(90 reference statements)
1
76
0
Order By: Relevance
“…Such field distributions can be generated, for instance, by tight focussing of polarized light beams [7][8][9][10] . To guarantee high quality and resolution in the investigation of objects with sub-wavelength dimensions, the precise knowledge of the spatial distribution of the exciting vectorial field is of utmost importance.…”
mentioning
confidence: 99%
“…Such field distributions can be generated, for instance, by tight focussing of polarized light beams [7][8][9][10] . To guarantee high quality and resolution in the investigation of objects with sub-wavelength dimensions, the precise knowledge of the spatial distribution of the exciting vectorial field is of utmost importance.…”
mentioning
confidence: 99%
“…Although the definitions of extinction, scattering and absorption cross sections typically employed for plane wave excitation cannot be applied to focused beams, one can calculate the power scattered and absorbed by the particles and 4 their sum (henceforth considered as extinguished power) by proper integration of the Poynting vectors. 38 Explicit expressions for the expansion coefficients for the incident field as well as for the scattered, absorbed and extinguished power are given in the Methods section.…”
Section: Resultsmentioning
confidence: 99%
“…Since the numerical aperture of the system is moderate, these results are quantitatively similar to the case of plane wave excitation. 38 39 Next, we assume that the lens is illuminated by an AP beam. In this case the spectra are dominated by a resonance at 2.76 eV.…”
Section: Resultsmentioning
confidence: 99%
“…In the present work we consider also other illuminations schemes that can be implemented in the same calculation scheme by expanding the incident field in vector spherical harmonics. Thus, a focused plane wave can be treated with the multipolar expansion developed by Sheppard and Török, 40 that has been used to study the influence of tight focusing on the plasmon spectra of single particles 41 and particle dimers 39 . As the degree of focusing increases, the relative weight of high order vector spherical harmonics decreases 40,41 .…”
Section: Methodsmentioning
confidence: 99%
“…However, control on the excitation of different multipolar orders can be addressed by adjusting the illumination conditions. It has been shown that higher order resonances can be quenched by using strongly focused beams, both in single particles 41 and particle clusters 39 . We can consider the effect of focused plane waves by the extension of the generalized Mie theory described in Section 2.…”
Section: Illumination Conditionsmentioning
confidence: 99%